PENGEMBANGAN PERANGKAT PENGAJARAN MATEMATIKA DENGAN PENDEKATAN PMR BERBANTUAN CD INTERAKTIF PADA MATERI PERSAMAAN LINEAR SATU VARIABEL KELAS VII - Zaenal Mutaqin, Ikin (Universitas Wiralodra, 2016)
This  study  aimed  to  develop  and produce devices PMR mathematics learning approach   aided   interactive   CD   on   the material linear equations class VII are valid and effective. The result of the development of mathematics learning with PMR approach on  the  material  linear  equations  of  one variable  of  class  VII  shows  the  validation results  of the experts. Implementation field learning device that has generated valid and effective   tool   with   active   variable   and process skills, reaching thoroughly studied, the effect of active variable and process skills to the learning outcomes and no difference between    the    control    group    and    the implementation   class.   Once   implemented obtained  that  result  is  students  achieve  a complete study with KKM = 65 gained 79.8 completeness. There is an active variable and process  skills  influence  on  the  process  of student learning outcomes by 79.3%. There are  differences  between  the  control  group (66.7) and the implementation class (78.0). It concluded that the study of mathematics by PMR  approach  aided  interactive  CD  on material class VII PLSV valid and effective.